2013
DOI: 10.1098/rspb.2013.0711
|View full text |Cite
|
Sign up to set email alerts
|

‘Manipulation’ without the parasite: altered feeding behaviour of mosquitoes is not dependent on infection with malaria parasites

Abstract: Previous studies have suggested that Plasmodium parasites can manipulate mosquito feeding behaviours such as probing, persistence and engorgement rate in order to enhance transmission success. Here, we broaden analysis of this ‘manipulation phenotype’ to consider proximate foraging behaviours, including responsiveness to host odours and host location. Using Anopheles stephensi and Plasmodium yoelii as a model system, we demonstrate that mosquitoes with early stage infections (i.e. non-infectious oocysts) exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(168 citation statements)
references
References 23 publications
13
152
3
Order By: Relevance
“…Plasmodium parasites have been shown to manipulate their hosts at different stages of the parasite's life cycle ( [16,56], but see [57]). In particular, we previously reported that infected birds attract significantly more mosquitoes than uninfected ones, possibly through the emission of distinct olfactory signals [16].…”
Section: (C) Virulence In Birds and Mosquito Transmissionmentioning
confidence: 99%
“…Plasmodium parasites have been shown to manipulate their hosts at different stages of the parasite's life cycle ( [16,56], but see [57]). In particular, we previously reported that infected birds attract significantly more mosquitoes than uninfected ones, possibly through the emission of distinct olfactory signals [16].…”
Section: (C) Virulence In Birds and Mosquito Transmissionmentioning
confidence: 99%
“…Combining data for these two species to estimate vital rates would not necessarily generate realistic inference. Furthermore, data and research are particularly needed to better understand the influence of environmental factors on key parameters such as the EIP [89], vector competence [94,113], biting behaviour and interactions with infection [118,119], because these have been very under-researched to date.…”
Section: (B) Challenges In Understanding Climate Change Effects On Vementioning
confidence: 99%
“…(iii) Infection does not alter vector behavior, although this does occur for some pathogen/vector combinations (Auld and Tinsley 2015; but see Cator et al 2013). (iv) There are no density-dependent thresholds of vector-host ratio, though this can occur if hosts respond to high vector densities by increased grooming behavior and/or immune response to bites (Levin and Fish 1998;Darbro and Harrington 2007; but see also Charlwood et al 1995).…”
Section: Model Assumptionsmentioning
confidence: 99%